Gender Differences in Language and Their Impact on English Learning Strategies - Sudewi, Ni Ketut Putri Nila; Andaru Widhi, Bidari (Lingual Journal of Language and Culture, 2025)
This study examines gender differences in English communication among university students, focusing on reluctance to speak with the opposite sex, opinion expression, classroom participation, group work preferences, and language improvement strategies. The research aims to explore how gender influences students’ confidence and participation in English learning. Using a mixed-methods approach, data were collected through questionaries, class observations and interviews. The study applies Lakoff’s (1975) theory on gendered language and Tannen’s (1990) framework on communication style differences. The findings reveal that female students hesitate to speak English with male peers more than male students do. Female students prefer written expression, whereas males favour verbal communication. Additionally, female students tend to remain passive in class, while males actively participate. In terms of group work, female students favour same-sex collaboration, whereas males prefer mixed-gender teams. Regarding language improvement, female students believe they learn better through same-sex interactions, whereas males favour opposite-sex practice. These differences suggest that confidence, social norms, and classroom dynamics significantly impact English learning. The study highlights the need for gender-responsive teaching strategies to ensure equal participation and enhance students’ language skills.